Quaternary Structure of Fur Proteins, a New Subfamily of Tetrameric Proteins - Pérard, Julien; Covès, Jacques; Castellan, Mathieu; Solard, Charles; Savard, Myriam; Miras, Roger; Galop, Sandra; Signor, Luca; Crouzy, Serge; Michaud-Soret, Isabelle; de Rosny, Eve (Biochemistry (Easton), 2016)
The ferric uptake regulator (Fur) belongs to the family of the DNA-binding metal-responsive transcriptional regulators. Fur is a global regulator found in all proteobacteria. It controls the transcription of a wide variety of genes involved in iron metabolism but also in oxidative stress or virulence factor synthesis. When bound to ferrous iron, Fur can bind to specific DNA sequences, called Fur boxes. This binding triggers the repression or the activation of gene expression, depending on the regulated genes. As a general view, Fur proteins are considered to be dimeric proteins both in solution and when bound to DNA. In this study, we have purified Fur from four pathogenic strains (Pseudomonas aeruginosa, Francisella tularensis, Yersinia pestis, and Legionella pneumophila) and compared them to Fur from Escherichia coli (EcFur), the best characterized of this family. By using a series of “in solution” techniques, including multiangle laser light scattering and small-angle X-ray scattering, as well as cross-linking experiments, we have shown that the Fur proteins can be classified into two groups, according to their quaternary structure. The group of dimers is represented by EcFur and YpFur and the group of very stable tetramers by PaFur, FtFur, and LpFur. Using PaFur as a case study, we also showed that the dissociation of the tetramers into dimers is necessary for binding of Fur to DNA, and that this dissociation requires the combined effect of metal ion binding and DNA proximity.